CURTAILMENT OF EDUCATIONAL POTENTIAL OF RUSSIAN REGIONS - N. A. EKIMOVA (Высшее образование в России)
Russia’s economic development is extremely uneven. This statement is also applicable to the development of higher education system in Russia. What is the situation in the regions? The article examines the educational potential of the subjects of the Russian Federation on the basis of eleven year practice in the preparation of Educational rating of Russian regions. The rating indicators cover the different participants in the higher education market and allow to draw conclusions about their interest in the development of education in the region. The presence of the concentric model of the distribution of educational services in the regions, and the active process of “collapse” of the “educational bubble” that arose in Russia by 2008. In addition, the results of the analysis of the Educational rating of Russia regions are compared with the findings in another rating product – Rating of the academic activity of Russian regions. It is noted that some of the regions evidently underutilize the existing educational potential.